Contemporary Maritime Piracy in Southeast Asia History, Causes and Remedies - Young, Adam J. (ISEAS Publishing, 2007)
This book explores contemporary maritime piracy in Southeast Asia, demonstrating the utility of using historical context in developing policy approaches that will address the roots of this resurgent phenomenon. The depth and breadth of historical piracy help highlight causative factors of contemporary piracy, which are immersed in the socio-cultural matrix of maritime-oriented peoples to whom piracy is still a "thinkable" option. The threats to life and property posed by piracy are relatively low, but significant given the strategic nature of these waterways that link the Pacific and Indian Oceans, and because piracy is emblematic of broader issues of weak state control in the littoral states of the region. Maritime piracy will never be completely eliminated, but with a progressive economic and political agenda aimed at changing the environment from which piracy is emerging, it could once again become the exception rather than the rule